Demographic policies for large families in Greece: an opinion survey and implications for the social administration - Stamoulis, Dimitrios S.; Lambrou, Dimitrios N. (Advances in Social Sciences Research Journal, 2021)
Opinion surveys as a tool for policy formation and effectiveness testing in the area of demographic / family policies is rather neglected, although it may reveal significant perceived effectiveness and preference rankings by the recipients of these policies, giving a strong indication of what works best for families who are thinking of or have already been accredited the status of a large family. In an era of demographic decline and fiscal constraints, demographic / family policies need to be focused on what parents consider as important in order to affect their decisions. Given that the demographic decline has a negative cascading effect on several aspects of economy, society and personal life, selecting the policies that work best according to parents’ views who are the decision makers in these policy field, should be an imperative for governments nowadays.